Cover Image, Volume 16, Issue 2. Issue 2 (11th May 2022) - Unknown
Abstract : On the cover : Soybean breeding field at the J. Phil Campbell Sr. Research and Education Center, University of Georgia. See Z. Li et al., "Registration of G11‐7013 soybean germplasm with high meal protein and resistance to soybean cyst nematode, southern root‐knot nematode, and stem canker, " https://doi.org/10.1002/plr2.20204 . Photo by Michael S. Lucas.